2017
DOI: 10.1177/0263092317717586
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the vibro-isolation properties of horizontal seat suspension

Abstract: In this paper, an effective procedure of shaping the vibro-isolation properties of seat suspension system is presented. The simulation model is created to determine the dependence of evaluation criteria to the design parameters by means of which the system characteristics are formed. The developed optimisation procedure allows to find Pareto-optimal system configuration for the conflicted vibro-isolating criteria, i.e. the frequency weighted transmissibility factor used to evaluate dynamic seat comfort based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…e mathematical models of the basic forces in the system, that is, the spring force F cx1 , the force from end-stop buffers F cx2 , the force of hydraulic shock absorber F dx1 , and the overall friction force of suspension system F dx2 , have been shown in the author's previous paper [17]. In this paper, similar model has been formulated and experimentally verified for the purpose of optimizing the vibroisolation properties of horizontal seat suspension.…”
Section: Rank Input Factorsmentioning
confidence: 99%
“…e mathematical models of the basic forces in the system, that is, the spring force F cx1 , the force from end-stop buffers F cx2 , the force of hydraulic shock absorber F dx1 , and the overall friction force of suspension system F dx2 , have been shown in the author's previous paper [17]. In this paper, similar model has been formulated and experimentally verified for the purpose of optimizing the vibroisolation properties of horizontal seat suspension.…”
Section: Rank Input Factorsmentioning
confidence: 99%
“…Values of normalized quality indices J sh;n calculated according to equations (15) and (16) for the passive suspension and Skyhook algorithm are presented in Figure 14. Obviously, lower values of the quality index are desired as they correspond to better vibration mitigation.…”
Section: Analysis Of Ride Comfortmentioning
confidence: 99%
“…Settings of the vehicle suspension system should be selected in a way which allows for isolation of passengers from unevenness while simultaneously maintaining control over the vehicle as was stated by Els et al 13 Uys et al 14 proposed a method of determining the parameters of vehicle suspension taking into account weighted root mean square vertical acceleration of driver and passenger. Maciejewski et al 15 presented methods for optimization of parameters of horizontal seat suspension and for improvement of dynamic seat comfort and the suspension travel by shaping the suspension's vibro-isolation properties. However, especially demanding cases are those where ride comfort and handling are simultaneously required, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related studies have shown that the human body is a complex resonance system, especially sensitive to low frequency vibration [9][10][11][12][13]. When the vibration and shock caused by various excitations of road surface and engine are transmitted to the cab through the frame, it will cause complex vibration coupling characteristics.…”
Section: Introductionmentioning
confidence: 99%